2018
DOI: 10.1126/science.aaq1736
|View full text |Cite
|
Sign up to set email alerts
|

Cell type transcriptome atlas for the planarian Schmidtea mediterranea

Abstract: The transcriptome of a cell dictates its unique cell type biology. We used single-cell RNA sequencing to determine the transcriptomes for essentially every cell type of a complete animal: the regenerative planarian Planarians contain a diverse array of cell types, possess lineage progenitors for differentiated cells (including pluripotent stem cells), and constitutively express positional information, making them ideal for this undertaking. We generated data for 66,783 cells, defining transcriptomes for known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
607
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 377 publications
(703 citation statements)
references
References 93 publications
(91 reference statements)
25
607
0
1
Order By: Relevance
“…FISH for mp-1 and mhc-2 showed that all DVM co-expressed both markers; however, some cells around intestinal branches expressed only mp-1 (Figure 1E; Figure S1E,F). Moreover, the recently described marker dd_12771(PTPRD) [13] had enriched expression in cluster 6 (Figure 1F), and FISH showed that dd_12771(PTPRD) + cells also expressed mp-1 but not mhc-2, indicating that cluster 6 represents IM (Figure 1F; Figure S1E,F). Finally, pharynx muscle marker (dd_8356) expression [13, 15] was restricted to cluster 7, which was therefore considered pharynx muscle (Figure 1C).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…FISH for mp-1 and mhc-2 showed that all DVM co-expressed both markers; however, some cells around intestinal branches expressed only mp-1 (Figure 1E; Figure S1E,F). Moreover, the recently described marker dd_12771(PTPRD) [13] had enriched expression in cluster 6 (Figure 1F), and FISH showed that dd_12771(PTPRD) + cells also expressed mp-1 but not mhc-2, indicating that cluster 6 represents IM (Figure 1F; Figure S1E,F). Finally, pharynx muscle marker (dd_8356) expression [13, 15] was restricted to cluster 7, which was therefore considered pharynx muscle (Figure 1C).…”
Section: Resultsmentioning
confidence: 79%
“…Moreover, the recently described marker dd_12771(PTPRD) [13] had enriched expression in cluster 6 (Figure 1F), and FISH showed that dd_12771(PTPRD) + cells also expressed mp-1 but not mhc-2, indicating that cluster 6 represents IM (Figure 1F; Figure S1E,F). Finally, pharynx muscle marker (dd_8356) expression [13, 15] was restricted to cluster 7, which was therefore considered pharynx muscle (Figure 1C). In summary, we identified transcriptomes for four main classes of muscle: BWM (including longitudinal and circular fibers), DVM, IM, and pharynx muscle.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations